Variability in practice patterns in stress urinary incontinence and pelvic organ prolapse: results of an IUGA survey - Kammerer-Doak, Dorothy; Svabik, Kamil; Bazi, Tony (International urogynecology journal, 2017)
INTRODUCTION AND HYPOTHESIS: Members of the International Urogynecological Association (IUGA) come from different geographic locations and practice settings. A member survey regarding practice patterns provides valuable information for practitioners and researchers alike, and allows the IUGA to discover areas to focus on education and information dissemination. METHODS: A questionnaire was developed by the IUGA Research and Development committee and distributed electronically to IUGA surgeons. Answers were analyzed in reference to demographics, geographic distribution, and academic affiliation. RESULTS: Five hundred sixty-four members answered the questionnaire, representing a 28 % response rate, and closely reflecting the geographic distribution of IUGA membership. Preferred surgical treatment for uncomplicated SUI was the mid-urethral trans-obturator sling (49.7 %). Vaginal mesh was mainly used for repair of recurrent POP (20.4 %). Pessary use was offered "always" or "frequently" by 61.5 %, with no difference in academic affiliation, but significant differences based on region of practice. Compared to practitioners in non-academic centers, those with academic affiliation utilized Urodynamic studies (UDS) and Magnetic Resonance Imaging (MRI) more frequently in the evaluation of POP. Regions of practice significantly influenced the majority of practice patterns, with the highest impact found in the use of robotic assistance. CONCLUSIONS: Many practice patterns in the evaluation and treatment of POP and SUI depend on academic affiliation and geographic location. Practice patterns are not always based on most recent evidence-based data.
Keywords: Magnetic Resonance Imaging; Surveys and Questionnaires; Gynecology; magnetická rezonanční tomografie; Humans; suburetrální pásky; Pelvic floor disorders; Academic practice; lidé středního věku; chirurgické síťky; Practice patterns; Surgical Mesh; Female; mladý dospělý; dospělí; internacionalita; Internationality; Ultrasonography; lidé; Suburethral Slings; Urinary Incontinence, Stress; průzkumy a dotazníky; Adult; stresová inkontinence moči; ultrasonografie; ženské pohlaví; Male; Middle Aged; Pessaries; Practice Patterns, Physicians'; urologie; lékařská praxe - způsoby provádění; Young Adult; prolaps pánevních orgánů; Urodynamic studies; Stress urinary incontinence; gynekologie; Physician survey; mužské pohlaví; Urology; Pelvic Organ Prolapse; pesary